Some Relations Between the European Union Budget and the Budgets of Member Countries in the Context of the Two Crisis (Financial Crisis of 2008, Pandemic Crisis – Covid -19) - Data Analysis - Florina POPA (Communications of International Proceedings, 2023)
The paper pursues the experience of the economies of some European Union countries, in the context of the two crises - the financial one of 2008 and respectively, the pandemic –  COVID 19, from the perspective of the analysis of some macroeconomic indicators. The motive behind the study is given by the author's intention to observe some aspects regarding the evolution of the relationship between the European Union budget and the budgets of some Member States, in the context of the two types of crises.The intention of the originality of the work can be considered from the chosen theme that aims to capture the effects of the two crises reflected in the indicator data over a certain time interval; the data are observed at the level of the budgets of the analysed Member Countries, in relation to the budget of the European Union. The research methodology was the documentation from the specialty literature, for formulate ideas and interpretate in the author’s own vision, as well as the analysis of statistical data referring to budget revenues and expenditures of Member States. The findings of the paper capture some situations observed following-up the analysis of budget indicators regarding the relationship between the budgets of some Member States and the budget of the European Union. One can observe the implications of the two crises on the revenue and expenditure budgets of each Member State in relation to the EU budget, a guiding element in taking recovery measures, as the case may be.
Keywords: European Union budget; Member Countries; expenditures; revenues; deficit; surplus.